Neutralizing monoclonal antibodies to fight HIV-1: On the threshold of success - Jaworski, Juan Pablo (2017)
Anti-human immunodeficiency virus type-1 (anti-HIV-1) neutralizing monoclonal antibodies are broadening the spectrum of pre- and post-exposure treatment against HIV-1. A better understanding of how these antibodies develop and interact with particular regions of the viral envelope protein is guiding a more rational structure-based immunogen design. The aim of this article is to review the most recent advances in the field, from the development of these particular antibodies during natural HIV-1 infection, to their role preventing infection, boosting endogenous immune responses and clearing both free viral particles and persistently infected cells.